(untitled) (Research, Society and Development, 2022)
It is estimated to have an increasing incidence of Cervical Cancer (CC) in the world, the third cause of malignant neoplasm among women in Brazil. O PCCU exam is available at the basic health unit, but there are many women who do not perform it, making CC prevention actions a relevant challenge to public health. This study analyzed the reasons for low adherence to Pap smear in Basic Health Units (BHU). Quali-quantitative research method was used, applying the exploratory nature through a well-structured online questionnaire, on the Google Forms platform, distributed via link through social networks, to women residing in the municipality of Redenção-PA, with age between 20-64 years, with active sexual life. The adherence to the exam reached 75%, but 23.46% of women did not undergo the exam in the last three years. In addition, 20.38% said they only perform it when they have a symptom, while 15.38% do not, mainly by the feeling of shame and fear (8.84%). It is worth mentioning that 70.38% prefer carrying out through the private sector, where 23.08% justify not having time to attend during the week, and 21.54% use the delay in receiving the result as a justification. The need for campaigns and programs regarding the importance of the exam was evidenced, that can reach women with no time available during the week, such as carrying out PCC on weekends at least once a month, possibly contributing to the adhesion of these users.